Analisis Big Five Personality Dalam Pemilihan Parfum - Tsani, Ahmad; Zulfiningrum, Rahmawati (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
Perfume has become a primary need for every person, and its use has various purposes both according to needs and according to personality category. This research aims to examine perfume aromas and the personality spectrum, with a focus on how the choice of perfume aroma can reflect individual characteristics on various personality spectrums. The research used a qualitative descriptive approach by conducting in-depth interviews and observations of informants who used various types of perfume. The research results show that the choice of perfume aroma can reflect certain aspects of a person's personality. Floral aromas tend to be associated with feminine characteristics, while woody or spice aromas may be associated with masculine characteristics. Apart from that, there is a close relationship between the choice of perfume aroma and the level of extraversion, neuroticism, openness, familiarity and emotional stability of the perfume user.Understanding the relationship between perfume aroma and the personality spectrum of perfume users can be useful in developing the perfume industry. Using perfume that is tailored to personality preferences can improve the perfume user's experience and help express their personality through the chosen aroma.